Carrying the Family in the Body: Family Trajectories of Paraguayan Women in the Paraná Tri-Border Area. (April 2022) - Guizardi, Menara; Nazal, Esteban; Magalhães, Lina
This article discusses the results of ethnographic case studies on female cross-border experiences in the Paraná Tri-Border Area (between Argentina, Brazil, and Paraguay) conducted in 2018 and 2019. Reclaiming the life histories of thirty Paraguayan women, we will analyze the tensions that lie between family trajectories, female transgenerational acquisition of cultural and social capitals, rural-urban and transborder mobility, and labor insertion. Our analysis will explore more in-depth the impact that productive and reproductive work overloads have on different generations of women who share family bonds, showing how their care responsibilities are intrinsically related to their agency strategies.